1948
DOI: 10.1128/jb.55.5.693-703.1948
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Biotin and Oxybiotin by Lactobacillus pentosus 124-2

Abstract: The demonstration of biotin activity for microorganisms of such analogs of biotin as oxybiotin (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

1950
1950
1976
1976

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…For M. echinata and S. atra desthiobiotin is inactive, but combined with biotin it has the same growth-promoting activity as an amount of biotin equal to the total weight of the mixture (Perlman, 1948a). The biotin activity of 0-heterobiotin has been demonstrated for Lactobacillus arabinosus, L. casei, Saccharomyces cerevisae, R. trifolii (Winnick et al, 1945;Pilgrim et al, 1945;Rubin, Flower, et al, 1945;Duschinsky et al, 1945), for clostridia (Perlman, 1948b;Shull and Peterson, 1948), for M. echinata and S. atra (Perlman, 1948a), and for L. pentosus (Krueger and Peterson, 1948).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…For M. echinata and S. atra desthiobiotin is inactive, but combined with biotin it has the same growth-promoting activity as an amount of biotin equal to the total weight of the mixture (Perlman, 1948a). The biotin activity of 0-heterobiotin has been demonstrated for Lactobacillus arabinosus, L. casei, Saccharomyces cerevisae, R. trifolii (Winnick et al, 1945;Pilgrim et al, 1945;Rubin, Flower, et al, 1945;Duschinsky et al, 1945), for clostridia (Perlman, 1948b;Shull and Peterson, 1948), for M. echinata and S. atra (Perlman, 1948a), and for L. pentosus (Krueger and Peterson, 1948).…”
Section: Discussionmentioning
confidence: 94%
“…This analog has been shown to act as an inhibitor to both biotin and 0-heterobiotin for L. casei (Dittmer and du Vigneaud, 1944; Lilly and Leonian, 1944;Tatum, 1945;Rubin, Drekter, and Moyer, 1945;Rubin, Flower, et al, 1945). However, desthiobiotin is inactive for Lactobacillus arabino8us, Lactobacillus pentosus, and Rhizobium trifolii either when alone or when biotin is present (Lilly and Leonian, 1944;Krueger and Peterson, 1948). For M. echinata and S. atra desthiobiotin is inactive, but combined with biotin it has the same growth-promoting activity as an amount of biotin equal to the total weight of the mixture (Perlman, 1948a).…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have shown that bacteria and yeast remove biotin from various growth media (9,15,18), but in such studies the mechanism of biotin transport was not determined. The present work was initiated to characterize the biotin transport process in Saccharomyces cerevisiae.…”
mentioning
confidence: 99%
“…Oxybiotin, an analogue of biotin in which the sulfur is replaced by an oxygen atom, has been shown to be as effective as biotin in promoting the growth of lactobacilli (5,8,10). Unlike other biotin analogues, oxybiotin functions without being converted to biotin (1).…”
Section: Resultsmentioning
confidence: 99%
“…We reported that Lactobacillus plantarum converts biotin sequentially to an avidin-combinable and -uncombinable vitamer, the latter being impermeable to the organism (1). Krueger and Peterson (8) have reported that a similar organism, L. pentosus, degrades biotin to products not utilizable by Saccharomyces cerevisiae, which suggests that no vitamers accumulated. They demonstrated, also, that oxybiotin undergoes the same degradative process.…”
mentioning
confidence: 99%